MORAL VALUES OF CLAY JENSEN IN “13 REASONS WHY” NOVEL BY JAY ASHER - Dea Ayu Rosmaningtyas; Muh. Kholiq (Universitas Gunadarma, 2022)
The research attempts to find out the characteristics of moral value based on one of the main characters. This research used descriptive qualitative method. The writer also used other information which related to the research problems. The writer used Bertens moral values theory that stated four characteristics such as responsibility, pure heart, obligation and formality to find out the moral values in novel “13 Reasons Why.” After analyzing the data, the writer found some types of moral values such as, responsibility, pure heart, obligation, and formality.